Alternative splicing responses to salt stress in Glycyrrhiza uralensis revealed by global profiling of transcriptome RNA-seq datasets - Yao, Hua; Li, Guozhi; Gao, Zhuanzhuan; Guo, Fei; Feng, Jianghua; Xiao, Guanghui; Shen, Haitao; Li, Hongbin (Frontiers in Genetics, 2024)
Alternative splicing (AS) plays a vital role in enhancing protein diversity through post-transcriptional regulation. While several studies have investigated the impact of AS on plant stress responses, the mechanisms by which AS interacts with transcriptional regulation to modulate the salt stress response in G.uralensis remain poorly understood. To address this, we employed high-throughput RNA sequencing to comprehensively analyze AS events in G.uralensis under salt stress at various time points.We observed AS events in G.uralensis under salt stress, with exon skipping being the Alternative splicing response to salt stress 2 predominant AS type. A total of 4117 genes in the aerial part (AP) and underground parts (UP) of G.uralensis showed notable AS regulation when exposed to salt stress at different time intervals. The modulation of primary and secondary metabolic processes of proteins and organic substances under salt stress is significantly influenced by AS in G.uralensis. In reaction to salt stress, there was significant enrichment of differentially spliced genes in pathways related to RNA transport, mRNA surveillance, and spliceosome. Both the aerial part (AP) and underground parts (UP) of G.uralensis displayed splicing regulation of genes, resulting in AS events under salt stress conditions. These findings imply that salt-responsive AS, directly and indirectly, governs G.uralensis salt response.Further investigations into AS function and mechanism during abiotic stresses may offer novel policy for bolstering plant to respond to stress.